2022
DOI: 10.1021/acs.est.2c07195
|View full text |Cite
|
Sign up to set email alerts
|

Wild Bee Exposure to Pesticides in Conservation Grasslands Increases along an Agricultural Gradient: A Tale of Two Sample Types

Abstract: Conservation efforts have been implemented in agroecosystems to enhance pollinator diversity by creating grassland habitat, but little is known about the exposure of bees to pesticides while foraging in these grassland fields. Pesticide exposure was assessed in 24 conservation grassland fields along an agricultural gradient at two time points (July and August) using silicone band passive samplers (nonlethal) and bee tissues (lethal). Overall, 46 pesticides were detected including 9 herbicides, 19 insecticides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 52 publications
0
15
1
Order By: Relevance
“…arable land) has been linked to both declines in flying insects and increased insect exposures to pesticides [5,15,16]. A study conducted concurrently with the present study found that concentrations and number of pesticides detected with above-ground passive samplers within conservation grasslands increased with proportion of cropland proximal to those grasslands (radius 1 km), although it found no relationship between proportion of proximal cropland and pesticide residues (number or concentration) in bee tissues at these sites [17]. In addition, the number of pesticides detected in the tissues of flying insects collected in nature conservation areas in Germany was related to the proportion of agricultural production area in a 2 km radius around the reserves [15].…”
Section: Introductioncontrasting
confidence: 58%
See 4 more Smart Citations
“…arable land) has been linked to both declines in flying insects and increased insect exposures to pesticides [5,15,16]. A study conducted concurrently with the present study found that concentrations and number of pesticides detected with above-ground passive samplers within conservation grasslands increased with proportion of cropland proximal to those grasslands (radius 1 km), although it found no relationship between proportion of proximal cropland and pesticide residues (number or concentration) in bee tissues at these sites [17]. In addition, the number of pesticides detected in the tissues of flying insects collected in nature conservation areas in Germany was related to the proportion of agricultural production area in a 2 km radius around the reserves [15].…”
Section: Introductioncontrasting
confidence: 58%
“…We previously showed that there was a positive relationship between proportion of agriculture proximal to conserved grassland fields and pesticide concentrations accumulated on silicone bands at a site (a.k.a., ‘pesticide exposure') [17]. Pesticide exposure did not differ between CRP-other and CP42 fields [17]. Summed (total) pesticide concentration and summed insecticide concentration at a site were not significantly correlated due to the relatively low concentrations of insecticides compared with other compounds such as herbicides (see §2.6).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations